Adjuvants in fungicide spraying in wheat and soybean crops - Garcia, Luiz C. (2016)
The objective of this study was to determine whether the combination of adjuvants to fungicides significantly alters the spray physicochemical characteristics, and potentiates the chemical control of foliar diseases, in that it may affect yield components in wheat (Triticum aestivum) and soybean (Glycine max). The experimental design was completely randomized for the spray physicochemical characteristics, and randomized blocks for the culture variables analyzed, with four treatments and five replications. Treatments consisted of control (no fungicide spraying in the shoot), with fungicides only in plant shoots, fungicides + 0.25% of the spray with adjuvant of methyl ester base of soybean oil, and fungicides + 0.05% of the spray with adjuvant lauryl ether sodium sulfate base. Treatments were applied with land boom sprayer in wheat (season 2012) and soybean (season 2013). The variables evaluated were spray physicochemical characteristics, incidence and severity of diseases and yield components. Adjuvants altered the spray surface tension. Adding lauryl ether sodium sulfate to spray significantly reduced the disease severity in wheat, and incidence in soybean cultivation. The addition of adjuvants to spray fungicide did not affect yield components in both cultures.